Effects of automated fiber placement defects on high strain rate compressive response in advanced thermosetting composites. (December 2021) - Trochez, Alexander; Jamora, Von Clyde; Larson, Richard; Wu, K. Chauncey; Ghosh, Dipankar; Kravchenko, Oleksandr G
The effects of fiber tow gaps, overlaps, and folds on the compressive strength of a fiber-placed composite laminate under dynamic loading conditions are investigated in this work. These layup defects were placed in the 0° fiber direction within a 24-ply quasi-isotropic laminate with a [45/0/–45/90]3S stacking sequence. Different locations of the defect were considered, namely near the bottom (in the 2nd ply), middle (10th ply) and top (23rd ply) of the laminate. High-strain rate compression experiments were conducted on composite that are pristine and with embedded defects using a split Hopkinson pressure bar (SHPB). The results were used to determine the strength knockdown due to the local changes in ply morphology because of fiber bed compaction in the presence of a layup defect. The experimental results revealed the anisotropy of in-plane strength coinciding with the deposited defect orientation. No significant variations in the residual strength were observed regarding the location of the defect (i.e., bottom, middle, or top) within the laminate. A morphological analysis based on microtomography of the cured defects indicates that the sources of the strength knockdown are due to the 0° ply drop-off, fiber misalignment in the adjacent 90° and 45° degree plies and the resin-rich region formed at the corner of the tapered 0° ply, between +45° and –45° laminas. The present study indicates the increased role of local morphological ply variations on the strength of composites under high-strain rate loading conditions, which should be considered during composite design.